(−)‐R‐Mevalonolactone Studied by ROA and SERS Spectroscopy. Issue 9 (16th January 2014) - Chruszcz‐Lipska, Katarzyna; Jaworska, Aleksandra; Szczurek, Ewelina; Baranska, Malgorzata
ABSTRACT Here we present for the first time the experimental and theoretical (DFT/B3LYP/6‐311++G**) Raman optical activity (ROA) spectra of (−)‐R‐mevalonic acid as the δ‐lactone form in neat liquid and in the aqueous solution. Quantum chemical calculations show the conformational diversity of (−)‐R‐mevalonolactone originated from small energy differences between the various conformation of the six‐membered ring and the arrangement of the hydroxyl group. According to calculations, the investigated compound takes predominantly the chair conformation with the hydroxyl group in axial position, but the contribution of the other chair and boat conformers in the equilibrium at room temperature is not negligible. Additionally, we present normal Raman and the surface enhanced Raman (SERS) spectra of (−)‐R‐mevalonolactone adsorbed on the colloidal silver. Chirality 26:93–101, 2014. © 2014 Wiley Periodicals, Inc.